Lembaga Seniman dan Budayawan Muslimin Indonesia: Perannya Dalam Pengembangan Budaya Islam di Indonesia Era 1962-1967 M - Nor Huda; Wahyu Amni; Fitriah Fitriah (Tanjak: Sejarah dan Peradaban Islam, 2022)
LESBUMI stands for Indonesian Muslim Artists and Cultural Institute. This institution was established on June 28, 1962. The LESBUMI organization is one of the autonomous bodies of NU which is engaged in the fields of culture and arts. The LESBUMI organization has an important role in competing with LEKRA, and controlling the national film industry. In addition, this institution is used as a bridge for da'wah using art media. LESBUMI develops Islamic arts, such as: gambus music, Islamic theater, dance, literature and makes a film that is a form of LESBUMI's renewal of NU residents, namely the film Call of the Holy Land. Negative culture originating from the West continues to try to be countered by cultural movements and also boycotts against films originating from abroad.